2019
DOI: 10.1021/acs.jpcc.8b11874
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Surface Carbonyl- and Hydroxyl-Group Concentrations on Electrode Kinetics in an All-Vanadium Redox Flow Battery

Abstract: This study investigates the effect of thermal activation of all-vanadium redox flow battery (RFB) carbon-felt electrodes on their electrode kinetics. Using X-ray photoelectron spectroscopy, thermal activation is shown to increase the content of the C−OH group, decrease the content of the CO group, and not affect the O−CO group, with all these surface moieties already being present in the nonactivated carbon felt. Rotating disk electrode studies were performed using custom electrodes fabricated using the carb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
49
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 65 publications
3
49
0
Order By: Relevance
“…[1][2][3] It is widely accepted that OFGs work as an effective catalyst towards the occurring redox reactions in a vanadium flow battery (VFB). [4][5][6][7] This has sparked a lot of scientific as well as industrial activities, which focus on the optimization of the carbon-based electrodes by various oxidative treatments. Several surface treatment methods have been reported to increase the activity of the felt electrode by employing OFGs using thermal, chemical, electrochemical, acid or alkaline activation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] It is widely accepted that OFGs work as an effective catalyst towards the occurring redox reactions in a vanadium flow battery (VFB). [4][5][6][7] This has sparked a lot of scientific as well as industrial activities, which focus on the optimization of the carbon-based electrodes by various oxidative treatments. Several surface treatment methods have been reported to increase the activity of the felt electrode by employing OFGs using thermal, chemical, electrochemical, acid or alkaline activation.…”
Section: Introductionmentioning
confidence: 99%
“…For many electrochemical applications that utilize graphitic materials such as batteries, electrolyzers, or supercapacitors, surface‐active oxygen functional groups (OFGs) at the electrode are considered essential [1–3] . It is widely accepted that OFGs work as an effective catalyst towards the occurring redox reactions in a vanadium flow battery (VFB) [4–7] . This has sparked a lot of scientific as well as industrial activities, which focus on the optimization of the carbon‐based electrodes by various oxidative treatments.…”
Section: Introductionmentioning
confidence: 99%
“…A recent attempt was made to sort out these inconsistencies by employing rotating disk electrode techniques on thermally treated carbon electrodes. [ 52 ] This study reported that the thermal activation of carbon substrates inhibits V(IV)/V(V) kinetics, but enhances the V(II)/V(III) reaction rate. The enhancement was attributed to the presence of COH groups on thermally treated carbon.…”
Section: All‐vanadium Rfbmentioning
confidence: 99%
“…[9][10][11][12] A lot of scientific and industrial activities regarding VFBs focus on improving graphite-based felt electrodes by the application of OFGs through oxidative treatments such as thermal, chemical, electrochemical, alkaline or acid activation, to facilitate the negative (V III + e − ⇌ V II , E 0 = −0.26 V vs. SHE) and positive (V V O2 + + 2 H + + e − ⇌ V IV O 2+ + H2O, E 0 = 1.0 V vs. SHE) half-cell reactions. [13][14][15][16][17][18][19][20][21] The later observed performance enhancement is then ascribed to an elevated quantity of surface oxygen. 5,22 However, there are contradictory results about the specific OFG (hydroxyl, carbonyl, or carboxylic group), which is suspected to be responsible for the increased activity.…”
Section: Introductionmentioning
confidence: 98%